Со планирање до развој во медиумите – состојби и перспективи во Република Македонија - Билбиловска, Ивана (Економски факултет, УКИМ, Скопје, 2012)
Planning in the media is a philosophy of behaviour of the medium, based on the need for continuous thinking about its future. One of the forms of planning in the medium is the program plan, constructed according to the goals, vision and strategy of the media house. The investments in the program depend on the purchasing power of the medium. The goal of the program planning is to attract a larger audience with smaller investments. The preapration of the schedule for program broadcasting in the domestic media is called program scheme. Advertisments are a part of it. Therefore planning is an art used in building image of the media, while securing financial resources. The success of the progam scheme is determined by the budget, its planning, the increase in number of employees and in the target audience. The achieved rating indicates the programme efficiency, which should justify the costs. The planning depends on performed analyses and assessments of numerous internal and external factors. This should be a guide for action, decrease of uncertainty and the risk. The doctoral paper emphasizes the role of program planning, media planning and advertisements as the most important source of revenues of the media.
Thru planning to media development – situation and perspectives in Republic of Macedonia
Докторска дисертација одбранета во 2012 година на Економскиот факултет во Скопје, под менторство на проф. д–р Нада Секуловска.
Keywords: planning, programme planning, media planning, strategies, advertisements, tactics and revenues of media